Virtual View Image over Wireless Visual Sensor Network - Nyoman Putra Sastra; Wirawan Wirawan; Gamantyo Hendrantoro (Universitas Ahmad Dahlan, 2011)
In general, visual sensors are applied to build virtual view images. When number of visual sensors increases then quantity and quality of the information improves. However, the view images generation is a challenging task in Wireless Visual Sensor Network environment due to energy restriction, computation complexity, and bandwidth limitation. Hence this paper presents a new method of virtual view images generation from selected cameras on Wireless Visual Sensor Network. The aim of the paper is to meet bandwidth and energy limitations without reducing information quality. The experiment results showed that this method could minimize number of transmitted imageries with sufficient information..